A study of high-sensitivity C- reactive protein and trop-T in patients with coronary artery disease - Rathore, Anita; Pareek, Umesh; Sharma, Avdhesh (International Journal of Research in Medical Sciences, 2016)
Background: The diagnosis of Hs-CRP levels is helpful to correlate with the clinical severity of coronary artery disease and with coronary events in both acute and sub-acute phase of myocardial ischemia. Coronary heart disease (CHD) is the major cause of death in the developed world. The level of certain proteins in plasma increase during acute inflammatory state or secondary to certain types of tissue damage. Methods: 100 subjects and 50 controls were taken from the outdoor and indoor department of medicine in Geetanjali Medical College & Hospital, Udaipur, Rajasthan, India. C-reactive protein was estimated by immuno-turbidometry method. Results: We have also come across very high levels of Hs-CRP in the CAD patients and found that the value of Hs-CRP was 2.51±0.79 mg/L as compared to 0.76±0.34 mg/L in control and therefore the rise in Hs-CRP is highly significant because of p value (0.0001). Conclusions: Hs-CRP is highly significant in CAD patients when compared to the control group. It is an independent and better predictor of CAD.